The economics of entrepreneurship - Parker, Simon C.; Parker, Simon C. (New York : Cambridge University Press, 2009)
'Entrepreneurship is an integral part of economic change and growth. Yet until recently it has been largely neglected by economists. In The Economics of Entrepreneurship, Simon C. Parker draws on theoretical insights and recent empirical findings to show how economics can contribute to our understanding of entrepreneurship. The book is based on an earlier work, The Economics of Self-employment and Entrepreneurship (Cambridge University Press, 2004), that has quickly become an essential reference for academics researching the economics of entrepreneurship. Written in a more accessible style, this book contains much that made this earlier work so successful and, in addition, includes improved pedagogical features and new material on the theory of the firm, spin-offs, nascent entrepreneurship, growth-enhancing knowledge spillovers and social entrepreneurship. It can be used both as a reference text for academics from a variety of disciplines and as a textbook for graduate students'--Provided by publisher.
Includes bibliographical references (p. 466-540) and index.
Keywords: Entrepreneurship; Managerial economics; New business enterprises -- Management